2008
DOI: 10.1007/s11096-008-9209-4
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge and attitude of the Turkish community pharmacists toward pharmacovigilance in the Kadikoy district of Istanbul

Abstract: The results show that Turkish community pharmacists have poor knowledge about pharmacovigilance. There is an urgent need for educational programs to train them about pharmacovigilance and ADR reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
107
1
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(175 citation statements)
references
References 10 publications
60
107
1
7
Order By: Relevance
“…This tallies, to a large extent, with other reports from Nigeria, China and Malaysia [9,18,21]. While it is important to note that these studies were carried out among physicians, several other studies involving pharmacists have indeed confirmed that under-reporting of ADRs is common to all health care professionals [22,23]. It is also interesting to note the non-response of medical consultants and the low level of participation by pharmacists in this study.…”
Section: Discussionsupporting
confidence: 80%
“…This tallies, to a large extent, with other reports from Nigeria, China and Malaysia [9,18,21]. While it is important to note that these studies were carried out among physicians, several other studies involving pharmacists have indeed confirmed that under-reporting of ADRs is common to all health care professionals [22,23]. It is also interesting to note the non-response of medical consultants and the low level of participation by pharmacists in this study.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have shown that the rate of reporting ADRs by pharmacists in different countries varied from 3% to 14.7% which is lower than what was reported in this study. 20,23 The reasons for the pharmacists nonreporting of adverse drug reactions mainly included uncertainty about causality, not sure of the adverse drug reactions to report, not having access to adverse drug reactions reporting form, ignorance of the rule of reporting, the complexity of the form, lack of time and workload. The determinants of under-reporting of adverse drug reactions as shown from our study is in line to a large extent with other reports from Nigeria, China, Spain, and Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge and attitudes of community pharmacists towards pharmacovigilance and adverse drug reactions in Kadikoy district of Istanbul, Turkey, were scrutinized by Toklu and Uysal [4]. The results demonstrated Turkish pharmacists had poor knowledge on pharmacovigilance, and they stressed on an urgent need for educational programs for training professionals about pharmacovigilance and ADR reporting [4].…”
Section: Discussionmentioning
confidence: 99%